Rancang Bangun Sistem Informasi Akademik Sekolah Tinggi Ilmu Hukum Tambun Bungai Berbasis Web - Ardeanto, Robert; Putra, Putu Bagus Adidyana Anugrah; Christian, Efrans (Journal of Information Technology and Computer Science, 2023)
Tambun Bungai College of Law (STIH-TB) has quite a lot of students but the academic process is still done manually. This manual process makes it difficult to present information if it is needed at any time and can be hampered if an error occurs in the required data so that it will result in wasted time. Based on these problems, a website-based Academic Information System (SIAKAD) is needed so that the Tambun Bungai School of Law (STIH-TB) can facilitate the process of academic activities so that they become more effective and efficient. The method used in this research is the Extreme Programming method. There are four stages that must be done in the extreme programming (XP) method, namely planning for problem identification, design for system modeling, coding is the implementation stage or program code creation, and testing to find out what errors arise when the website is running. This research produces an academic information system website that is useful for the Tambun Bungai law school so that it can help the academic process.